La Croix-Rouge américaine et la Belgique. - Jones, Leonard Chester (Genève : Croix-Rouge, 1919)
Bibliotheek E. Anseele
Extr. de la Revue Internationale de la Croix-Rouge, I, 3, 15 mars 1919, 268-286
Frans
Brochure